Biodiversity in Numbers: Update on Species Knowledge in Costa Rica (Biocenosis, 2021)
To preserve and use biodiversity in a sustainable way, it is fundamental to know it. This is the reason why data is presented for some taxonomic groups of Costa Rica. Information was collected, analyzed, and systematized in workshops, specialist consultations and publication reviews. Information is presented in an integrated and simple way, comparing numbers between 2014 and 2019 as an upgrade for the following taxonomic groups: insects, fungi, lichen, plants, fish, amphibians, reptiles, birds, and mammals. Furthermore, information gaps are mentioned. Among the main results, for 2019 the number of most vertebrate groups had risen, with fish as the one which had the biggest increment. For amphibians, reptiles, birds, and mammals, the increment was lower because of the taxonomic revisions that allowed the entry but also the elimination of some registrations. The number of insects as well as arthropods are in revision. The number of plant and fungi decreased because of taxonomic rectification for both groups. However, separating fungi from lichen, the last one had a significative increment. Information generated is fundamental to begin a baseline of serious, reliable, and up to date data about our biodiversity.
Keywords: biological diversity; conservation; species data; taxonomic groups; information gaps